DYNAMIC CHARACTERISTICS OF MECHANICAL COMPONENTS INSIDE THE BALL MILL HOUSING - Jumanazarov , Akmal; Egamberdiev , Ilkhom; Saibov , Maruf (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article investigates the dynamic characteristics of key mechanical components of a ball mill operated at the enterprises of the Navoi Mining and Metallurgical Combine (NMMC). The vibrational loads acting on the bearing supports, drive system, and mill housing lining are analyzed. Using the finite element method (FEM) and spectral analysis, resonance frequencies, zones of dynamic stress concentration, and causes of accelerated wear have been identified. Recommendations are provided to reduce vibrations and extend the service life of the equipment